ANALISIS HAMBATAN WIRAUSAHA MARTABAK DI KABUPATEN TEGAL - Rosadi, Fitra; Hendaryati, Neni; Nafiati, Dewi Amaliah (Universitas Muhammadiyah Gresik, 2020)
This study aims to investigate the factors inhibiting interest in entrepreneurship, especially in martabak entrepreneurs in Lebaksiu District, Tegal Regency. As the object of this research is in Lebaksiu Subdistrict which is divided into17 villages, researchers used sample three villages namely Lebaksiu Lor, Lebaksiu Kidul and Kajen. Descriptive qualitative methods is a method applied in this research. The data collection techniques used are with observation, interviews, and documentation techniques. The results showed that the inhibiting factors in martabak entrepreneurship concisted of factors originating from internal and external factors. Detected internal factors arise from within the entrepreneur martabak such as personal characteristics, experience, ability to control a business and capital factors. The second inhibiting factor is an external factor, which this factor comes from outside the private entrepreneur martabak which includes the environment, recruitment of employees who are proficient in martabak making and promotion to the mass media.